Self-learning Guide for Bioloid Humanoid Robot Assembly with Elements of Augmented Reality to Support Experiential Learning in Sauro Research Seeding (2019)
A self-learning guide for assembly robots BIOLOID PREMIUM in human form is presented, where elements of augmented reality are included in order to facilitate the process of assembly and manipulation of prototypes. This guide was evaluated with students belonging to the research seeding SAURO (research seeding in Automation and Robotics) of the Institución Universitaria Pascual Bravo.